2020
DOI: 10.1139/cjps-2019-0173
|View full text |Cite
|
Sign up to set email alerts
|

Strategic timing and rate of phosphorus fertilization improves phosphorus-use efficiency in two contrasting cultivars of subirrigated greenhouse-grown chrysanthemum

Abstract: Greenhouse floriculture operations pose significant environmental risk due to extensive inputs of fertilizer, especially nitrogen and phosphorus (P). Recent evidence shows that the use efficiency for nitrogen or sulphur is markedly improved in subirrigated potted chrysanthemums (Chrysanthemum morifolium Ramat.) by supplying a moderate level of the nutrient during vegetative growth, and removing the entire nutrient suite at the onset of reproductive growth, without adverse effects on plant quality. Here, two sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Our early research on the nutrition of greenhouse-grown pot chrysanthemums used Sonneveld's solution as the industry standard, and confirmed that the production of market-quality plants and flowers is unaffected by removing entire nutrient supplies at bud break, and by supplying N and P levels as low as 9.3 and 1.3 mmol L 1 , respectively, during vegetative growth. (Shelp et al 2017(Shelp et al , 2020b. We also demonstrated that N/P/K levels (in mmol L 1 ) as low as 4.3 N, 0.65 P and 2.3 K produces market-quality plants with acceptable leaf N/P/K levels of 4.05.5% DM, 0.610.75% DM and 4.2-5.2% DM, respectively (Shelp et al 2020a;Shelp, B.J.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Our early research on the nutrition of greenhouse-grown pot chrysanthemums used Sonneveld's solution as the industry standard, and confirmed that the production of market-quality plants and flowers is unaffected by removing entire nutrient supplies at bud break, and by supplying N and P levels as low as 9.3 and 1.3 mmol L 1 , respectively, during vegetative growth. (Shelp et al 2017(Shelp et al , 2020b. We also demonstrated that N/P/K levels (in mmol L 1 ) as low as 4.3 N, 0.65 P and 2.3 K produces market-quality plants with acceptable leaf N/P/K levels of 4.05.5% DM, 0.610.75% DM and 4.2-5.2% DM, respectively (Shelp et al 2020a;Shelp, B.J.…”
Section: Discussionmentioning
confidence: 63%
“…These findings indicate that the macronutrient use efficiencies (which can be defined as mg shoot DM/concentration of macronutrient supply) improved approximately 4-fold with decreasing macronutrient supplies. Based on our previous research on the N, P and sulphur nutrition of chrysanthemums, the primary mechanism for sustaining plant shoot growth with decreasing N/P/K supplies was likely enhanced acquisition or uptake efficiency, but given our experimental methodology, it was not possible here to quantify the relative importance of acquisition and internal utilization efficiencies (Shelp et al 2017(Shelp et al , 2020a(Shelp et al , 2020bSutton et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our research, we improved NUE in modern cultivars of greenhouse-grown, subirrigated chrysanthemums, without adversely affecting crop production. The entire macro-and micronutrient supplies were removed during reproductive growth, and only 25-50% of the recommended industry levels of macronutrients were provided during vegetative growth, together with the recommended industry level of micronutrients (MacDonald et al 2014;Shelp et al 2017Shelp et al , 2020Shelp et al , 2021bSutton et al 2019;Duncan Stephens et al 2021).…”
mentioning
confidence: 99%